Biological Pathways as Substantiation of the Use of Copper Radioisotopes in Cancer Theranostics - Niculae, Dana; Dusman, Ramona; Leonte, Radu A.; Chilug, Livia E.; Dragoi, Cristina M.; Nicolae, Alina; Serban, Radu M.; Niculae, Dragos A.; Dumitrescu, Ion B.; Draganescu, Doina (Frontiers in Physics, 2021)
Copper is a bioelement, cofactor for many enzymes, being involved in main biochemical processes; although high levels of copper promote proliferation of the cancer cells. Further development of radiopharmaceuticals based on copper radioisotopes depends on the understanding and taking advantage of its biochemical pathways in oncologenesis. As for other radiometals used in molecular imaging and/or targeted therapy, biological vectors are employed to transport the copper radioisotopes to target, aiming high specific uptake to tumour sites and precise delivery of ionizing radiation. Evidence of clinical utility of copper radioisotopes in ionic form, CuCl2 was also proved for in vivo study of the copper metabolism, guiding personalized copper-chelating treatment in cancer patients, or to image pathological sites associated to copper imbalance. Five of the copper radioisotopes gained interest for nuclear medicine applications, based on their emissions, energies and half-lives, as they can be produced with pharmaceutical-grade quality. The uptake mechanism, kinetics and metabolic parameters are important findings in molecular imaging, becoming decisive when designing individualized targeted radiotherapy, for dose calculations of high linear energy transfer (LET) Auger electrons and β- emissions of 64Cu and 67Cu. As radiation deposit high amount of energy within the intra-cellular space, the biochemical involvements of copper determine the targets, in drug design and validation. The biochemical pathways depict copper metabolism in normal cells and highlight its increased activity in tumour progression and angiogenesis. The avid uptake of copper into inter- and intra-mitochondrial spaces, as constituent of cytochrome C oxidase, substantiate the selection of 64/67CuCl2 as theranostic agents.